FITNAH SEBAGAI PENGHALANG AHLI WARIS: Studi Komparatif Pasal 173 Kompilasi Hukum Islam dan Hukum Islam - Muhammad Jufri; Riski Riko (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2020)
Slander is a barrier to being an heir, in the compilation of Islamic law, especially in article 173 it includes slander as a barrier to becoming an heir, basically the barrier of heirs agreed by the ulama 'there are three slaves, murder and different religions so there is no opinion about slander as heir barrier. Kompilasi Hukum Islam (KHI) is only used in Indonesia, in taking the argument that makes the slander a barrier to heirs is appropriate, and in accordance with the Qur'an, hadith, ijma'and especially the qiyas. According to the author's view of defamation as one of the barriers to inheriting in accordance with Islamic law.